Characterisation of a laser plasma betatron source for high resolution x-ray imaging. (13th July 2021) - Finlay, O J; Gruse, J-N; Thornton, C; Allott, R; Armstrong, C D; Baird, C D; Bourgeois, N; Brenner, C; Cipiccia, S; Cole, J M; Gregory, C; Jamison, S; et al.
Abstract: We report on the characterisation of an x-ray source, generated by a laser-driven plasma wakefield accelerator. The spectrum of the optimised source was consistent with an on-axis synchrotron spectrum with a critical energy of 13.8 − 1.9 + 2.2 keV and the number of photons per pulse generated above 1 keV was calculated to be 6 − 0.9 + 1.2 × 10 9 . The x-ray beam was used to image a resolution grid placed 37 cm from the source, which gave a measured spatial resolution of 4 µ m ×  5 µ m. The inferred emission region had a radius and length of 0.5 ± 0.2 µ m and 3.2 ± 0.9 mm respectively. It was also observed that laser damage to the exit aperture of the gas cell led to a reduction in the accelerated electron beam charge and a corresponding reduction in x-ray flux due to the change in the plasma density profile.